Mortality in vitamin K antagonist-related intracerebral bleeding treated with plasma or 4-factor prothrombin complex concentrate - Majeed, Ammar; Meijer, Karina; Larrazabal, Ramiro; Arnberg, Fabian; Luijckx, Gert J.; Roberts, Robin S.; Schulman, Sam (Thrombosis and Haemostasis, 2014)
Prothrombin complex concentrates (PCC) can rapidly normalise prolonged prothrombin time, induced by vitamin K antagonists (VKA). We conducted a multicentre retrospective study to investigate whether reversal of VKA coagulopathy with 4-factor PCC improves the survival of patients with VKA-related intracerebral haemorrhage as compared to plasma. We included 135 consecutive patients with VKA-related intracerebral haemorrhage treated either with plasma (mainly in Canada) or 4-factor PCC (The Netherlands and Sweden) for the reversal of VKA. Data on characteristics of the patients and the haemorrhage were collected. The volume of intracerebral haematoma was calculated from the first computed tomography (CT) scan. The unadjusted and adjusted odds ratio (OR) for 30-day all-cause mortality in both treatment groups was compared using logistic regression. Patients who received plasma (n=35, median 4 units) more often had diabetes, antiplatelet therapy, and intraventricular haemorrhage on the initial CT scans than patients who received PCC (n=100, median 22.5 IU/kg [interquartile range 20–26 IU], median of total dose 1,700 IU). The volume of intracerebral haematoma was larger in the plasma-treated group compared to the PCC-treated group (haematoma, mean 64.5 vs 36.0 cm3; p=0.021). The unadjusted OR for all-cause 30-day mortality in the PCC group was 0.40 (95% confidence interval, 0.18–0.87; p=0.021) compared to the plasma group. After adjusting for the haematoma volume, bleeding localisation and age, the effect of PCC on mortality became non-significant. In conclusion, treatment with 4-factor PCC for VKA reversal in patients with intracerebral haemorrhage does not seem to reduce the 30-day all-cause mortality compared to plasma.
Keywords: Vitamin K antagonists; intracerebral hemorrhage; prothrombin complex concentrates; plasma